Interval model of multi-criterion task of reengineering physical structures of distributed databases - Beskorovainyi, V.; Kolesnyk, L. (My University, 2021)
An interval mathematical model of a multicriteria task of reengineering physical structures of distributed databases is proposed. The model is built on the basis of the Kolmogorov-Gabor polynomial and the universal utility function of partial criteria. It provides an assessment of options for interval values of cost indicators, access time and network traffic. The use of the universal function of general utility makes it possible to more accurately take into account the preferences of the decision-maker. The use of a rational S-like utility function of partial criteria allows to reduce the time complexity of the procedures for calculating estimates. Practical application of the proposed model will improve the efficiency of automated design technologies for distributed databases
Keywords: design automation; interval model; multicriteria optimization; decision making; distributed database reengineering